Smoking versus vaping: how (not) to communicate their relative harms. Issue 2 (1st February 2021) - Ayton, Peter; Weiss-Cohen, Leonardo
Abstract: Here we consider how the relative harms of two nicotine products were communicated in a public health campaign. Following a peer-reviewed evaluation that rated the relative harm of a range of nicotine products relative to the harm of smoking, and which rated the relative harm of vaping as about 5% that of smoking (D. J. Nutt et al., 2014 European Addiction Research, 20 (5), 218–225), the UK government launched a campaign which transposed these relative harms into relative safety, promoting the message that "vaping is 95% safer than smoking". We discuss the communication issues arising from transposing a measure of relative harms into relative safety and report the results of an experiment which shows that significantly more people correctly appreciated the ratio of the relative harms from smoking and vaping after reading the statement "vaping is 5% as harmful as smoking" than after reading the statement "vaping is 95% safer than smoking". We discuss the policy implications of our findings.